Alva and Anders go to school: the problem of bullying and the anti-bullying strategies in Sweden - Daria Rybka-Koch (University of Lower Silesia, 2011)
The article reviews theoretical and practical approaches to the problem of bullying among students in Sweden. In the first part the paper presents the definition of bullying, it describes different forms and factors that affect the behaviour of bullies and victims. The legal regulations and restrictions adopted to prevent the problem of bullying and the activities of public institutions and Non Government Organizations in Sweden are also presented. The paper reviews recent research on the bullying in Sweden. The second part gives an overview on recent press information relevant to the problem. The author concludes with a summary of factors which impact the effectiveness of anti-bullying strategies based on the results of a government report on the broad study conducted in Sweden between 2007 and 2010.